Pertuzumab monotherapy after trastuzumab-based treatment and subsequent reintroduction of trastuzumab: activity and tolerability in patients with advanced human epidermal growth factor receptor 2-positive breast cancer - Cortés, Javier; Fumoleau, Pierre; Bianchi, Giulia Valeria; Petrella, Teresa M; Gelmon, Karen; Pivot, Xavier; Verma, Shailendra; Albanell, Joan; Conte, Pierfranco; Lluch, Ana; Salvagni, Stefania; Servent, Veronique; et al. (Journal of clinical oncology, 2012)
The combination of pertuzumab and trastuzumab resulted in a clinical benefit rate (CBR) of 50% in patients with human epidermal growth factor receptor 2 (HER2) -positive breast cancer whose disease progressed during prior trastuzumab-based therapy. To define whether this previously observed encouraging activity was a result of the combination of pertuzumab and trastuzumab or of pertuzumab alone, we recruited a third cohort of patients who received pertuzumab without trastuzumab. We then investigated the impact of reintroducing trastuzumab to patients whose disease progressed on pertuzumab monotherapy. Twenty-nine patients with HER2-positive breast cancer whose disease progressed during prior trastuzumab-based therapy received pertuzumab (840 mg loading dose, then 420 mg every 3 weeks) until progressive disease or unacceptable toxicity. Seventeen patients with disease progression continued to receive pertuzumab (at the same dose), with the addition of trastuzumab (4 mg/kg loading dose and then 2 mg/kg weekly or 8 mg/kg loading dose and then 6 mg/kg every 3 weeks). All 29 patients enrolled for pertuzumab monotherapy experienced disease progression. The objective response rate (ORR) and CBR were 3.4% and 10.3%, respectively, during pertuzumab monotherapy. With the addition of trastuzumab, the ORR and CBR were 17.6% and 41.2%, respectively. Progression-free survival was longer with combination therapy than pertuzumab monotherapy (17.4 v 7.1 weeks, respectively). Treatment was well tolerated with minimal cardiac dysfunction. Although pertuzumab has some activity in patients with HER2-positive breast cancer that progressed during therapy with trastuzumab, the combination of pertuzumab and trastuzumab seems to be more active than monotherapy.